2002
DOI: 10.1101/gad.982802
|View full text |Cite
|
Sign up to set email alerts
|

Proper development of relay somatic sensory neurons and D2/D4 interneurons requires homeobox genes Rnx/Tlx-3 and Tlx-1

Abstract: Trigeminal nuclei and the dorsal spinal cord are first-order relay stations for processing somatic sensory information such as touch, pain, and temperature. The origins and development of these neurons are poorly understood. Here we show that relay somatic sensory neurons and D2/D4 dorsal interneurons likely derive from Mash1-positive neural precursors, and depend on two related homeobox genes, Rnx and Tlx-1, for proper formation. Rnx and Tlx-1 maintain expression of Drg11, a homeobox gene critical for the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
124
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(138 citation statements)
references
References 60 publications
11
124
3
Order By: Relevance
“…On the other hand, in developing dorsal SC, Tlx1/ 3 and Lmx1b are extensively co-expressed with Prrxl1 [22,23]. Prrxl1 appears to depend more on Lmx1b than on Tlx1/3, as in Lmx1b null mice Prrxl1 expression was completely abolished [9], whereas in Tlx1/3 null mutant mice Prrxl1 expression was normally initiated but completely lost by E14.5 [19]. Our data, showing Prrxl1 represses its own expression, point to a role for this transcription factor in fine-tuning positive transcriptional activity of aforementioned transcription factors in developing DRG and dorsal SC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in developing dorsal SC, Tlx1/ 3 and Lmx1b are extensively co-expressed with Prrxl1 [22,23]. Prrxl1 appears to depend more on Lmx1b than on Tlx1/3, as in Lmx1b null mice Prrxl1 expression was completely abolished [9], whereas in Tlx1/3 null mutant mice Prrxl1 expression was normally initiated but completely lost by E14.5 [19]. Our data, showing Prrxl1 represses its own expression, point to a role for this transcription factor in fine-tuning positive transcriptional activity of aforementioned transcription factors in developing DRG and dorsal SC.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies in mice have shown that Prrxl1 expression in developing sensory neurons depends on the presence of several transcription factors such as Isl1 [11,30] and Pou4f1 (Brn3a) [11] in DRG, and Tlx1/3 [19] and Lmx1b [9] in dorsal SC. In addition, in cranial ganglia, Phox2b down-regulates Prrxl1, as revealed by increased Prrxl1 expression in Phox2b À/À mice [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the PNS, Tlx3, Drg11, and Islet1 are expressed in all sensory ganglia, visceral and somatic (14,20,30, and this work). In the CNS, Tlx3, Drg11, and Lmx1b are expressed in the precursors of the nTS (9,20,22), spinal and principal trigeminal nuclei (11,20,31,32), spinal dorsal horn interneurons (20,23,33). The expression of these transcription factors is neither strictly specific for sensory neurons [e.g., Tlx3 is expressed in sympathetic ganglia (14) and Lmx1b in serotonergic neurons (34)] nor inclusive of all sensory neurons, but largely biased toward them.…”
Section: Discussionmentioning
confidence: 99%
“…The very high endogenous serotonin levels occurring in monoamine oxydase A-deficient mice (Cases et al, 1995;Lajard et al, 1999) affect respiratory network maturation, but the resulting alterations are not drastic and do not affect pups' survival (Bou-Flores et al, 2000;Burnet et al, 2001), whereas the lack of A6 neurons in Phox2a mutants significantly alters the respiratory rhythmogenesis at birth and is lethal. The differentiation of NA central neurons during CNS development is controlled by several homeobox genes such as the two closely related members of the Phox/aristaless family of paired-class homeobox genes, the Phox2a and Phox2b transcription factors, and the homeodomain protein Rnx/Tlx3 and bHLH transcription factor Mash1 (Tiveron et al, 1996;Pattyn et al, 1997Pattyn et al, , 1999Pattyn et al, , 2000Hirsch et al, 1998;Lo et al, 1998;Qian et al, 2001Qian et al, , 2002. All of these genes are linked in transcriptional cascades controlling the NA phenotype, but their respective positions differ from one NA cell group to another; Rnx deletion compromises the formation of most NA groups but partly preserved that of A6, whereas Phox2a deletion leads to the agenesis of A6 but does not affect the other NA groups.…”
Section: Developmental and Pathological Aspectsmentioning
confidence: 99%